Construyendo ciudades inseguras: temor y violencia en Argentina - Lucía Dammert (EURE, 2001)
Two processes characterized Argentinean urban development during the90s: increasing crime and fear of crime, and the development of gatedcommunities. Both processes have consolidated a model of urbandevelopment based on the redefinition of public spaces as well as theimportance and development of private closed urbanization. Thus, publicsecurity has been called as the main reason for people to justify aprocess of sociospatial segregation that has deeper roots that should beanalyzed. In that sense, this article aims to open up a debate on theimportance of violence and fear of crime in the definition of the citiesown future.